A Case of Congenitally Corrected Transposition of the Great Arteries Discovered on Coronary Computed Tomography. (17th February 2013) - Marler, Adam T.; Slim, Jennifer N.; Batts, Travis; Watts, James; Slim, Ahmad M.
Abstract : Congenitally corrected transposition of the great arteries is a rare condition accounting for less than 1% of all congenital cardiac diseases. The fundamental nature of this condition involves a blend of atrioventricular as well as ventriculoarterial discordance. Congenitally corrected transposition of the great arteries is classically associated with three additional abnormalities, including ventricular septal defect, right ventricular outflow tract obstruction, and tricuspid valve abnormalities. Patients with this anomaly have been shown to exhibit reduced exercise tolerance as well as reduced health-related quality of life when compared to patients with normal cardiovascular anatomy. We present the case of a 33-year-old active duty lieutenant in the United States Air Force referred to the cardiology clinic for evaluation of valvular heart disease with subsequent discovery of congenitally corrected transposition of the great arteries on cardiac gated computed tomography.